Korelasi Antara Durasi QRS, Fungsi Ventrikel Kanan dan Disinkroni Ventrikel Kiri Pasca Koreksi Tetralogi Fallot - Retna Dewayani; Bambang Budi Siswanto; Poppy S Roebiono; Anna Ulfah Rahajoe; Indriwanto Sakidjan; Ganesja M Harimurti (Jurnal Kardiologi Indonesia, 2007)
Background. QRS duration has long been established as a strong predic-tor of sudden cardiac death in patients after surgical correction of Tetral-ogy of Fallot (TOF). Several factors has been correlated to QRS duration, i.e severity of pulmonal regurgitation and right ventricular volume after TOF correction. But there is no established relation between right ven-tricular function and QRS duration after surgical correction TOF.Objectives. We aimed to investigate the relation between QRS duration and right ventricular function and whether patients after TOF repair with right bundle branch block have left ventricular dissynchrony.Methods.50 patients with repaired TOF were studied. Right ventricular function were derived from tissue Doppler imaging Tei index. Left ven-tricular dissynchrony were derived from tissue Doppler imaging. The time interval between the onset of QRS complex and the onset of systolic ejec-tion was measured for six left ventricular basal wall, i.e septal, lateral, anteroseptal, posterior, anterior and inferior wall. Mechanical delay from septal to lateral wall, antero-septal to posterior wall and anterior to infe-rior wall was calculated. Measured data were correlated with QRS dura-tion.Results.There was relation between QRS duration and right ventricular function (P = 0.028, r = 0.44). Ten (20%) of the examined patients after TOF repair had LV dissnynchrony particularly in patients with RBBB and prolonged QRS duration (160 ± 9 ms).Conclusions.There is correlation between right ventricular function and QRS duration. Left ventricular dissynchrony may exist in patients after TOF repair with RBBB.